El cuerpo mutilado de la Gran Guerra. Discapacidad y género en el retorno de un aviador costarricense - Arias Mora, Dennis (CIICLA, Universidad de Costa Rica, 2019)
This article studies the experience of mutilation suffered by the aviator Tobías Bolaños Palma (1892-1953) in the Great War (1914-1918), contrasting the notions of (human) body in combatant countries that developed a model of disability rehabilitation with those of the press and the Costa Rican diplomats that followed the case. Using diplomatic reports, newspapers and cultural magazines, and considering the gender perspective that marked the physical experience of the war, Bolaños' entry into the French aviation is analyzed, as well as his bodily experience and the socio-political and physical meanings of his return to the country. It is concluded that, unlike the political and economic value that massive mutilation had among veterans' associations of some combatant countries, the individual case of Bolaños faced the social and corporal prejudice of Costa Rican diplomats, politicians, and media, and the ideological uses that the Tinoco dictatorship (1917-1919) made of his return, issues that Bolaños dodged in different ways.